PEMANFAATAN ALGORITMA QUEUE DALAM PENGATURAN PENJUALAN UNTUK PRODUK MINUMAN JC-JELLY CORNER - Novca Adam Pratama (2021)
The problem faced by a new brand, namely JC-Jelly Corner, which is engaged in the production of beverages, is constrained by data collection in its sales because it cannot handicap any drinks that have been successfully sold and is constrained in the queue of customers ordering which sometimes when there are many buyers who order irregularly. In this study, we need a web-based application that can help solve the above problems to be able to manage the existing order queue to be more regular in the queue, plus in this case the empty drink stock can be seen, there is no need to directly check the ordered drinks are available or out, to speed up the ordering process. In the queuing arrangement here, using a queue algorithm to regulate the first buyer to order he is the first to come out, the second buyer who orders then he will wait first until the first buyer has finished being served and so on until there are no more queues for orders. Buyers can only order and see if the order has been processed or is still waiting if the process is finished reading done.